'It's not necessary to have this board to learn English, but it's helpful': student and teacher perceptions of interactive whiteboard use - Johnson, E. Marcia; Ramanair, Joseph; Brine, John (Innovation in language learning and teaching, 2010)
The use of interactive whiteboard (IWB) technology has great potential to invigorate not just language teaching, but any subject in which students and teachers interact with learning content, sound or video in the classroom; however, few research projects have examined and documented IWB implementation in tertiary-level Computer-Assisted Language Learning (CALL) classrooms. In order to address gaps in existing CALL literature, this qualitative research project sought to capture and illuminate both students' and teachers' perspectives of what worked and what needed to be improved. In particular, we aimed to discover the types of changes that teachers made to their pedagogy and whether or not students' motivation and response to the CALL environment were affected, and in what ways. The research findings provided us with valuable insights into the types of personal transformations that both teachers and learners made within the IWB context and lead to a discussion in this paper of the mediation of praxis, affect and motivation. Implications of the findings for the conduct of future multimedia CALL research studies are also examined and discussed.